Structural Insights and Biological Activities of Furan-Based Drugs in the Treatment of Human Diseases - Mishra, Avinash Kumar; Singh, Kuldeep; Saha, Sunam; Bharadwaj, Harsh; Gupta, Jeetendra Kumar; Shah, Kamal; Kumar, Shivendra; Jain, Divya; Verma, Hritik (Combinatorial Chemistry & High Throughput Screening, 2025)
Neurodegenerative diseases present significant public health challenges, driving the search for innovative therapeutic strategies. This review explores the neuroprotective potential of furan-containing compounds, which are derived from various natural and synthetic sources. These compounds are observed for their diverse pharmacological activities, including antioxidant and anti-inflammatory properties. By scavenging free radicals and mitigating oxidative stress, they address a key aspect of neurodegeneration. Additionally, furan derivatives modulate inflammatory pathways, potentially reducing neuroinflammation, a critical factor in the progression of these disorders. The review also highlights the impact of these compounds on neuronal survival and regeneration, suggesting their role in promoting neurogenesis and enhancing neuronal plasticity. Their interactions with neurotransmitter systems further support their neuroprotective effects, particularly in maintaining synaptic function and neurotransmission. The potential applications of furan-containing compounds are discussed concerning specific neurodegenerative diseases, such as Alzheimer's and Parkinson's. Insights from preclinical studies and in vitro experiments underscore their therapeutic promise across various experimental models. While still in the early stages of research, the evidence suggests that furan-containing compounds could be valuable in developing effective interventions for neurodegenerative diseases. This review emphasizes the need for further investigation into these compounds to realize their potential as neuroprotective agents fully.
Keywords: antidepressant